The Possible Cause of Red Leaf Disease and its Effect on Barlinka Table Grapes - Saayman, D.; Lambrechts, J.J.N. (South African Journal of Enology and Viticulture, 2017)
The so-called red leaf (RL) phenomenon of Barlinka table grapes was investigated in the Hex River Valley, De Doorns. The symptoms of RL were found to resemble those of grapevine leafroll (GLR) disease to a certain extent, but also differed markedly from GLR in that initial reddening occurs in veins of apical leaves, with the typical downward curling of affected leaves not a distinctive feature. Like GLR, RL induces uneven and retarded ripening, small and shot berries, without colour in extreme cases, making the grapes worthless for export. Vine vigour is also seriously reduced. The cause of RL was found not to be a Ca deficiency as previously postulated and generally accepted. Foliar and soil applied Ca proved ineffective. Reciprocal grafting of red leaf-affected and heat-treated plant material showed that RL is associated with plant-transmissible pathogens, probably similar or belonging to viruses associated with GLR.